2022
DOI: 10.1161/jaha.121.024499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Racial Disparities in Preoperative Cardiovascular Evaluation and Surgical Outcomes in Patients Undergoing Metabolic and Bariatric Surgery: A Retrospective Cohort Analysis

Abstract: Background We investigated preoperative referral patterns, rates of cardiovascular testing, surgical wait times, and postoperative outcomes in White versus Black, Hispanic, or other racial or ethnic groups of patients undergoing metabolic and bariatric surgery. Methods and Results This was a single center retrospective cohort analysis of 797 consecutive patients undergoing metabolic and bariatric surgery from January 2014 to December 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One study reported differences in cardiovascular assessment before bariatric surgery after adjusting for baseline cardiovascular risk, with white patients receiving more extensive cardiovascular testing than non-white patients. 7 Furthermore, white patients received more stress testing and shorter wait times for surgery than non-white patients even after adjusting for markers of socioeconomic status, including insurance provider and income. 7 Advance care planning Advance care planning as part of the consent process and preprocedural readiness ensures patient care is aligned with their goals.…”
Section: Preoperative Planning and Medical Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…One study reported differences in cardiovascular assessment before bariatric surgery after adjusting for baseline cardiovascular risk, with white patients receiving more extensive cardiovascular testing than non-white patients. 7 Furthermore, white patients received more stress testing and shorter wait times for surgery than non-white patients even after adjusting for markers of socioeconomic status, including insurance provider and income. 7 Advance care planning Advance care planning as part of the consent process and preprocedural readiness ensures patient care is aligned with their goals.…”
Section: Preoperative Planning and Medical Optimizationmentioning
confidence: 99%
“…7 Furthermore, white patients received more stress testing and shorter wait times for surgery than non-white patients even after adjusting for markers of socioeconomic status, including insurance provider and income. 7 Advance care planning Advance care planning as part of the consent process and preprocedural readiness ensures patient care is aligned with their goals. Under-represented racial and ethnic groups often lack these important care plans.…”
Section: Preoperative Planning and Medical Optimizationmentioning
confidence: 99%
See 1 more Smart Citation